Evolution of service innovation in e–commerce based on the NK model. (1st January 2015) - Yuan, Zhe; Jiang, Guoyin
In this study, we employ an NK–based model to explore the evolution path of synergetic services in e–commerce. The proposed model can dynamically adjust to the changes in the synergetic services brands of e–commerce over time, including their technical and promotion capabilities. The simulation results show that enterprise nnovation fitness increases with an increase in interaction between service capacities. The fitness of moderately interdependent enterprises is greater than enterprises which are completely dependent. In order to gain an optimal level of innovation fitness, an enterprise can make appropriate adjustments, depending on the interdependence of its service capabilities. The innovation evolutionary path of synergetic services in e–commerce is proportionately in line with an S–curve. The system can forecast the macro–level evolution of a synergic service under real scenarios, and support competition–oriented enterprises' decision–making. The synergy of internal service elements can also improve the enterprises' performance in terms of innovation.